Analisis Kualitatif Kecemasan Berkomunikasi Mahasiswa Dengan Dosen Pembimbing Dalam Proses Bimbingan Skripsi - Fatmawati Fadli (STKIP Andi Matappa, 2017)
The phenomenon of anxiety experienced by graduate students not only because of the complexity of scientific research process, but also because of worrying to supervisor who guide as well as the methods used by supervisor during thesis guidance. Therefore, the purpose of this study was to analyze students’ communication anxiety with the supervisor in the process of thesis guidance. This research was a study using a qualitative methodology. Data collection techniques used were in-depth interviews and observation. The respondents involved were 2 and recruited through snowball sampling technique. The results found that the respondents experienced anxiety when communicated with the supervisor during the thesis guidance. Anxiety is caused by lack of communication skills and experience, reinforcement, degree of evaluation, subordinate status, and degree of dissimilarity.